2014
DOI: 10.1021/ja501204q
|View full text |Cite
|
Sign up to set email alerts
|

Spin Tuning of Electron-Doped Metal–Phthalocyanine Layers

Abstract: The spin state of organic-based magnets at interfaces is to a great extent determined by the organic environment and the nature of the spin-carrying metal center, which is further subject to modifications by the adsorbate-substrate coupling. Direct chemical doping offers an additional route for tailoring the electronic and magnetic characteristics of molecular magnets. Here we present a systematic investigation of the effects of alkali metal doping on the charge state and crystal field of 3d metal ions in Cu, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(84 citation statements)
references
References 60 publications
5
79
0
Order By: Relevance
“…Both the XAS and XMCD spectra of Mn, measured in a field of 1.1 T, present a rich multiplet structure with strongly anisotropic line shape. Such spectra are a fingerprint of the ground state of the Mn 2+ ions, which, in analogy with MnPc/ Ag(100) [70], we assign to a B 1g state with orbital occupation (b 2g ) 1 (e g ) 2 (a 1g ) 2 and intermediate spin S = 3/2. The fact that the XMCD/ XAS intensity ratio is quite small for this field and temperature, suggests that charge transfer and/or screening effects induced by the substrate significantly reduce the effective Mn magnetic moment compared to that expected of an isolated molecule.…”
Section: Single-decker Molecules On Ferromagnets: Mnpc/nimentioning
confidence: 92%
See 1 more Smart Citation
“…Both the XAS and XMCD spectra of Mn, measured in a field of 1.1 T, present a rich multiplet structure with strongly anisotropic line shape. Such spectra are a fingerprint of the ground state of the Mn 2+ ions, which, in analogy with MnPc/ Ag(100) [70], we assign to a B 1g state with orbital occupation (b 2g ) 1 (e g ) 2 (a 1g ) 2 and intermediate spin S = 3/2. The fact that the XMCD/ XAS intensity ratio is quite small for this field and temperature, suggests that charge transfer and/or screening effects induced by the substrate significantly reduce the effective Mn magnetic moment compared to that expected of an isolated molecule.…”
Section: Single-decker Molecules On Ferromagnets: Mnpc/nimentioning
confidence: 92%
“…The neutral unsupported [TbPc 2 ] 0 molecule has two spin systems: one strongly localized on the 4f states, with J = 6, and the other delocalized over the two Pc ligands due to an unpaired π electron with spin S = 1/2 [77]. Electron doping of MPc by alkali metals has been shown to induce site-selective filling of molecular orbitals, including the aromatic π-states delocalized over the Pc ligand [81], as well as changes of the spin of the metal centers and ligand field [70]. For YPc 2 adsorbed on Au(111) it has been found that Cs doping leads to the filling of a π orbital of the Pc ligand [82,83].…”
Section: Tbpc 2 On Li-and O-modified Ni Filmsmentioning
confidence: 99%
“…In a study of MnPc, FePc, NiPc and CuPc on Ag(1 0 0) [667], it was found that coadsorbed Li reduced the Fe, Ni and Cu centers to their formal monocations, while Mn maintained its formal dicationic state. Li was also reported to reduce the ligand field at the sites of Mn, Fe and Ni.…”
Section: Adsorption On Coinage Metal Substratesmentioning
confidence: 99%
“…Besides, transition metal (TM) 8-hydroxyquinoline small molecules TMQ x (TM¼Cr, Mn, Fe, Co, Ni, Cu, and Zn) may have intrinsic magnetic properties due to the partially occupied 3d states in TM atoms. However, unlike other magnetic single molecules with metal atoms in the center, such as metallo-phthalocyanines (MPcs) [17,18] and metallo-porphyrins (MPps) [19] which are widely and deeply investigated, 8-hydroxyquinoline-based complexes have not been broadly explored. Properties of some of these molecules remain unclear with only very few pioneer research works showing that these molecules are wide bandgap semiconductors with paramagnetic or diamagnetic behaviors [20,21].…”
Section: Introductionmentioning
confidence: 99%